Community forestry in Nepal: a model of common property resource management - Acharya, K.P. (Banko Janakari, 2017)
The management of common forest land as community forest in Nepal is in practice since 1978. Studies showing the linkages between community forestry and common property resource are scanty in the country. This article discusses characteristics of common property resources and the principles and practices of community forestry in Nepal which is an example of common property resource management between Government agencies and users (co-managers). Forest User Groups (FUGs ) are the institutions responsible to manage the common property.